Seasonal Variation in the Prevalence of Common Orthopaedic Upper Extremity Conditions - Warrender, William J.; Henstenburg, Jeffrey; Maltenfort, Mitchell; Lutsky, Kevin; Beredjiklian, Pedro K. (Journal of Wrist Surgery, 2018)
Introduction Seasonal variation in disease processes and injuries have been reported, but it is unclear if this variation exists in upper extremity disorders. The goal of this study is to characterize seasonal and weather variations in common upper extremity orthopaedic conditions.Methods This cross-sectional study reviewed 68,943 consecutive, new patient visits from January 2010 to September 2015 for carpal tunnel syndrome (CTS), trigger finger (TF), DeQuervain's tenosynovitis (DeQ), lateral epicondylitis (LE), hand arthritis (OA), and distal radius fractures (DRF). Presentation rates for each condition were compared across month, season, and various weather parameters.Results DRF, OA, and LE had a higher rate of presentation in the winter compared with all other seasons (p < 0.001). TF and DeQ showed no statistically significant seasonal differences. Higher barometric pressures were associated with higher rates of all of the diagnoses. Higher humidity was associated with lower rates of CTS, TF, DeQ, LE, and DRF (p < 0.001). There was no significant association between temperature levels or amount of precipitation.Discussion Although the precise mechanism remains unclear, there does appear to be an impact of winter, increased barometric pressure, and higher humidity on presentation rates. Further studies are needed to determine more conclusively why this occurs.Level of Evidence Level IV, cross-sectional study.
Keywords: distal radius fracture; carpal tunnel syndrome; trigger finger; Dequervain's tenosynovitis; lateral epicondylitis; arthritis; seasonal variation